2014
DOI: 10.1080/15401383.2014.897663
|View full text |Cite
|
Sign up to set email alerts
|

Using Sandtray as a Collaborative Assessment Tool for Counselor Development

Abstract: Scant information exists regarding informal assessment tools in the supervision of counselor trainees. In this article, we combine the approach of sandtray and the integrated developmental model (IDM) of supervision (Stoltenberg & McNeill, 2009) to assess 3 structures of supervisee development. Based on tenets of artistic inquiry, the use of sandtray promotes reflexivity for increased understanding of a supervisee's approach in counseling and allows for an artifact in documenting particular learning outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 7 publications
(8 reference statements)
0
19
0
Order By: Relevance
“…As noted above, the purported utility of ST as a creative arts intervention has been established in the counseling literature (Bratton, Ceballos, & Ferebee, 2009;Garrett, 2013Garrett, , 2015bIsom et al, 2015;Lyles & Homeyer, 2014;Nickum & Purgason, 2017;Paone et al, 2015), albeit, mostly conceptually. Despite the conceptual nature of ST within the counseling literature, multiple studies have empirically examined the process and benefits of ST within the counseling profession (Paone et al, 2015;Stark & Frels, 2014;Swank & Lenes, 2013). The use of ST has been documented across time and cultures, and has developed out of personal phenomenological hermeneutic research (De Domenico, 1988;Graham, Scholl, Smith-Adcock, & Wittmann, 2014).…”
Section: Sand Tray: a Creative Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…As noted above, the purported utility of ST as a creative arts intervention has been established in the counseling literature (Bratton, Ceballos, & Ferebee, 2009;Garrett, 2013Garrett, , 2015bIsom et al, 2015;Lyles & Homeyer, 2014;Nickum & Purgason, 2017;Paone et al, 2015), albeit, mostly conceptually. Despite the conceptual nature of ST within the counseling literature, multiple studies have empirically examined the process and benefits of ST within the counseling profession (Paone et al, 2015;Stark & Frels, 2014;Swank & Lenes, 2013). The use of ST has been documented across time and cultures, and has developed out of personal phenomenological hermeneutic research (De Domenico, 1988;Graham, Scholl, Smith-Adcock, & Wittmann, 2014).…”
Section: Sand Tray: a Creative Approachmentioning
confidence: 99%
“…Originally developed out of Lowenfeld's (1979) world technique and modified by Kalff (2004), ST has been purported to promote healing and growth, effectively respond to trauma, increase self-esteem, facilitate the counseling process and counteract resistance, and attend to culturally specific issues, such as gender and race (Chang, Ritter, & Hays, 2005;Paone et al, 2015). Stark and Frels (2014) suggested that ST also offers opportunities as a collaborative assessment for counselor development, especially with counselors-in-training. As an expressive arts supervision activity, ST provides a shared symbolic language for supervisee and supervisor, and can assist in exploring case conceptualization and counseling dynamics (Chang et al, 2005;Stark, Garza, Bruhn, & Ane, 2015), as well as increasing supervisee self-awareness and expression (Carnes-Holt, Meany-Walen, & Felton, 2014;Garrett, 2015a;McCurdy & Owen, 2008).…”
Section: Sand Tray: a Creative Approachmentioning
confidence: 99%
See 3 more Smart Citations